Health Volunteers Overseas: 30 Years of Leveraging International Partnerships to Strengthen Health Worker Capacity - Pinner, April; Kelly, Nancy A. (Frontiers in Education, 2017)
Health Volunteers Overseas (HVO) is a United States based non-profit that collaborates with over eighty universities and health institutions around the world to send volunteer health professionals to provide continuing education, train the trainer courses, professional support, and consultation on academic programs and curricula development. By establishing mutually beneficial partnerships, HVO is able to deliver effective models of collaborative education that contribute sustainable solutions to strengthen health workforce capacity in resource-scarce countries – ultimately improving health outcomes and the quality of life for millions throughout the world. This paper provides an overview of HVO, outlines the role of international partnerships within HVO’s structure, describes the processes used to select partners, and analyzes lessons learned around the key indicators of how to establish and maintain successful international partnerships in education and health worker capacity building.